Lignin flame retardant containing nitrogen, phosphorus and silicon as well as preparation method and application of lignin flame retardant
The lignin-based flame retardant containing nitrogen-containing phosphorus silicon was designed and synthesized through side chain modification, which solved the performance problems of phenolic foam after high temperature combustion, significantly improved its flame retardancy and mechanical properties, and reduced its dependence on petroleum resources.
Patent Information
- Application Number
- CN202411290109.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-02-25
AI Technical Summary
The existing phenolic foam is loose and has low strength after combustion at high temperature, and is prone to smoldering. At the same time, its flame retardant properties and compressive strength are often affected after modification and rely on non-renewable petroleum resources.
Through side chain modification design, an intrinsic lignin-based flame retardant containing nitrogen, phosphorus and silicon is synthesized. The flame retardant introduces alkyl long chains of nitrogen, phosphorus and silicon elements to improve the flame retardant properties and mechanical properties of phenolic foam, and participates in the phenolic condensation reaction through the phenolic structure to reduce the migration and exudation of flame retardant elements.
The flame retardant properties and mechanical properties of the modified phenolic foam are significantly improved, the stability and dispersion of the overall performance are enhanced, and the dependence on petroleum resources is reduced.
Smart Images

Figure CN119505276A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lignin processing technology and application, and specifically relates to a lignin flame retardant and a preparation method thereof and application in phenolic foam. Background Art
[0002] Phenolic foam is widely used in the engineering field because of its excellent thermal insulation and flame retardant properties. However, its mass residual rate after high-temperature combustion is very low, the carbon layer is loose and has low strength, and it is easy to smolder after leaving the flame. Moreover, phenol, as one of the main raw materials for the production of phenolic foam, 95% comes from non-renewable petroleum resources. Due to the increasingly serious problems of excessive consumption of fossil resources, climate change and large-scale greenhouse gas emissions, how to use renewable resources instead of petroleum-based products to prepare phenolic foam on the basis of optimizing foam performance has become a research direction.
[0003] Lignin is the second most common natural polymer after cellulose and the second largest biomass material in the plant kingdom, with an annual global production of about 50 million tons. However, most lignin is currently used as a low-cost fuel to generate heat through direct combustion. Therefore, the comprehensive utilization of lignin currently faces huge challenges. Lignin has a benzene ring structure, which also gives lignin a better rigid chain structure than other natural macromolecules. The rigid structure also increases its thermal decomposition temperature, thus having better heat resistance and better carbon formation ability, so lignin can be used as a flame retardant additive for most polymers. Lignin is an aromatic polymer composed of three phenylpropanols: p-hydroxyphenylpropanol, guaiacylpropanol and syringylpropanol. It is a promising source of phenols, aromatics and polyols. More importantly, lignin has a structure similar to that of petroleum phenolic compounds and is an ideal renewable resource to replace phenol in phenolic foams. In the past decade, some researchers have successfully prepared lignin-based phenolic foams using lignin instead of phenol, but the flame retardancy and compressive strength of some phenolic foams after modification are often negatively affected. As the requirements for the performance of phenolic foam in various fields become higher and higher, methods to improve the flame retardant properties of phenolic foam without reducing its compressive strength and other properties are receiving more and more attention.
[0004] On this basis, in order to simultaneously improve the mechanical properties and flame retardant properties of lignin-based phenolic foam, we synthesized an intrinsic lignin-based flame retardant containing nitrogen, phosphorus and silicon through side chain modification design. This flame retardant is cheaper than DOPO; and its phenolic structure can further participate in the phenolic condensation reaction, thereby introducing flame retardant elements into the phenolic resin, which has the characteristics of being difficult to migrate and seep out; in addition, the introduction of long alkyl chains containing nitrogen, phosphorus and silicon elements in the side chain can simultaneously improve the flame retardant properties and mechanical properties of phenolic foam. Summary of the invention
[0005] Technical problem to be solved: The present invention provides a nitrogen-phosphorus-silicon-containing lignin flame retardant and its preparation method and application. The intrinsic lignin flame retardant containing nitrogen-phosphorus-silicon is prepared by side chain modification. The price is low, and the flame retardant elements are introduced into the macromolecular structure. The flame retardant elements are tightly combined with the macromolecular structure, which reduces the risk of migration and exudation, thereby improving the stability and dispersibility of the overall performance; in addition, by introducing the alkyl long chain of the nitrogen-phosphorus-silicon flame retardant elements, the flame retardant properties and mechanical properties of the phenolic foam are significantly improved. Studies have shown that in the application of modified phenolic foam, the flame retardant properties and mechanical properties are significantly improved, which provides a theoretical basis for the high added value utilization of lignin.
[0006] Technical solution: A method for preparing a nitrogen-phosphorus-silicon-containing lignin flame retardant, comprising the following steps: suspending 2.7 g of lignin, 3-4 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 3.5-4.5 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of aromatic aldehyde in 50-100 mL of ethanol in proportion, reacting in a microwave reactor at 80° C. for 10 min, pouring the reaction solution into a NaOH solution, dropping concentrated HCl thereto to precipitate it, washing with 10% ethanol, and drying to obtain an intrinsic lignin-based flame retardant containing nitrogen-phosphorus-silicon.
[0007] The lignin is at least one of Kraft lignin, organic solvent lignin or enzymatic lignin.
[0008] The aromatic aldehyde is benzaldehyde, 4-methylbenzaldehyde, 4-ethylbenzaldehyde, 4-methoxybenzaldehyde or p-hydroxybenzaldehyde.
[0009] The preferred preparation method is to suspend 2.7g Kraft lignin, 4g 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4.5g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03g benzaldehyde in 90mL ethanol, and react at 80°C for 10min using a microwave reactor. After the reaction is completed, the reaction solution is poured into a 40wt.% NaOH solution, 38wt.% concentrated HCl is added dropwise thereto to precipitate it, and the lignin-based flame retardant is obtained by washing with 10wt.% ethanol and drying.
[0010] The nitrogen, phosphorus and silicon-containing lignin flame retardant prepared by the above preparation method.
[0011] Application of the nitrogen-phosphorus-silicon-containing lignin flame retardant in the preparation of phenolic foam.
[0012] The specific application method is to replace 10% of phenol with lignin flame retardant and prepare phenolic foam according to the phenol / formaldehyde molar ratio of 1:1.7; 28g of lignin flame retardant, 252g of phenol and 12.4g of deionized water are placed in a 65°C water bath, 120g of polyformaldehyde is added four times every 15 minutes, and the pH value of the mixture is adjusted to 8-9 with a 30wt.% NaOH solution; then react at 70°C for 2.5h, then heat to 92°C and keep for 10min, when the temperature drops to 85°C, add 18.6g of melamine to obtain a modified phenolic resin; then put the obtained phenolic resin, 4g of surfactant and 10.5g of foaming agent into a plastic container, add 28g of a mixed acid composed of water, sulfuric acid and phosphoric acid in a mass ratio of 1:1:1 under vigorous stirring to form a uniform mixture, quickly pour the obtained mixture into a mold, and heat it in an oven preheated at 75°C for 3 hours to complete the curing and foaming process.
[0013] Beneficial effects: ① The intrinsic lignin flame retardant containing nitrogen, phosphorus and silicon is prepared by side chain modification. The flame retardant elements introduced into the macromolecular structure are not easy to migrate and seep out, and the performance is more stable and the dispersibility is better; ② By introducing the alkyl long chain containing nitrogen, phosphorus and silicon flame retardant elements, it can play a toughening and flame retardant effect; ③ The flame retardant properties and mechanical properties of the modified phenolic foam are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The infrared spectra of enzymatic lignin and lignin flame retardant are shown in Figure 1. EHL is enzymatic lignin; NPSi-L is lignin flame retardant; 1700cm in enzymatic lignin -1 The absorption peak of carbonyl (C=O) stretching vibration is at 751cm; while in lignin flame retardant, the absorption peak disappears, indicating that carbonyl participates in the condensation reaction. -1 The absorption peak at 1097 cm -1 、1255cm -1 and 1048cm -1 The bands at 1139 cm -1 and 964cm -1 The bands at 1002 cm-1 are believed to be the stretching vibrations of Si-C and Si-O-Si. -1 The results show that lignin has successfully introduced nitrogen, phosphorus and silicon flame retardant elements.
[0015] Figure 2The XPS spectra of enzymatic lignin and lignin flame retardant are shown in Figure 1. EHL is enzymatic lignin; NPSi-L is lignin flame retardant. The XPS spectrum of enzymatic lignin shows that only C, N and O elements exist in enzymatic lignin, and the contents of C, N and O are 75.08, 3.62 and 21.3 wt.%, respectively. The lignin flame retardant contains five elements, C, O, N, P and Si, and the contents of C, O, N, P and Si are 73.31, 19.76, 4.08, 1.3 and 1.55 wt.%, respectively. Therefore, the XPS spectrum also proves that nitrogen, phosphorus and silicon flame retardant elements are successfully introduced into lignin.
[0016] Figure 3 This is the phosphorus spectrum of lignin flame retardant; there are two phosphorus peaks in the phosphorus spectrum, indicating that lignin is introduced into the DOPO structure in two ways.
[0017] Figure 4 is the limiting oxygen index of the phenolic foam modified by the lignin flame retardant in Example 15; as shown in the figure, the LOI of the pure phenolic foam PF is 29.6%; when the lignin flame retardant replacement rate is 5% and 10%, the limiting oxygen index of the foam increases to 47.5% and 51.2% respectively, and the addition of lignin-based flame retardants containing nitrogen, phosphorus and silicon can significantly improve the flame retardant properties of the phenolic foam.
[0018] Figure 5 It is the compressive strength of the phenolic foam modified by the lignin flame retardant in Example 15 at 10% strain. The compressive strength of pure phenolic foam is 0.12MPa; the study found that when the replacement amount is 5% and 10%, the compressive strength of the foam is 0.18MPa and 0.22MPa, respectively, which are better than PF foam. The main reason is that the introduction of long alkyl chains in the modified lignin helps to enhance the toughness of NPLFFX foam, thereby improving the compressive strength of the foam. Another reason is that when the substitution rate of lignin flame retardant is low (≤10%), the pore size of the foam pores is relatively small and uniform. DETAILED DESCRIPTION
[0019] The preparation method of nitrogen-phosphorus-silicon-containing lignin flame retardant comprises the following specific steps in proportion:
[0020] Step 1: 2.7 g of lignin, 3-4 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 3.5-4.5 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of aromatic aldehyde are suspended in 50-100 mL of ethanol, and reacted at 80° C. for 10 min using a microwave reactor. After the reaction is completed, the reaction solution is poured into a 40 wt.% NaOH solution, 38 wt.% concentrated HCl is added dropwise thereto to precipitate it, and the lignin-based flame retardant is obtained by washing with 10 wt.% ethanol and drying.
[0021] Step 2: Preparation of phenolic foam modified by nitrogen-phosphorus-silicon lignin flame retardant According to Chinese invention ZL202211702932.1, 5-10% of phenol is replaced by lignin flame retardant.
[0022] The above-mentioned lignin is any one or more of Kraft lignin, organic solvent-type lignin or enzymatic lignin; the above-mentioned aromatic aldehyde is benzaldehyde, 4-methylbenzaldehyde, 4-ethylbenzaldehyde, 4-methoxybenzaldehyde or p-hydroxybenzaldehyde; the above-mentioned modified phenolic foam is prepared with reference to Chinese invention ZL202211702932.1, and the phenol substitution rate is 5-10%.
[0023] Example 1
[0024] 2.7 g Kraft lignin, 3 g 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 3.5 g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g benzaldehyde were suspended in 50 mL ethanol and reacted at 80 ° C for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, 38 wt.% concentrated HCl was added dropwise to precipitate it, and the mixture was washed with 10 wt.% ethanol and dried to obtain a lignin-based flame retardant.
[0025] Example 2
[0026] 2.7 g Kraft lignin, 3.5 g 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 3.5 g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g 4-methylbenzaldehyde were suspended in 80 mL ethanol and reacted at 80 ° C for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, 38 wt.% concentrated HCl was added dropwise to precipitate it, and the lignin-based flame retardant was obtained by washing with 10 wt.% ethanol and drying.
[0027] Example 3
[0028] 2.7 g Kraft lignin, 3.5 g 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4 g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g 4-ethylbenzaldehyde were suspended in 90 mL ethanol and reacted at 80° C. for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, to which 38 wt.% concentrated HCl was added dropwise to precipitate it, and the solution was washed with 10 wt.% ethanol and dried to obtain a lignin-based flame retardant.
[0029] Example 4
[0030] 2.7 g Kraft lignin, 4 g 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4 g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g p-hydroxybenzaldehyde were suspended in 90 mL ethanol and reacted at 80 ° C for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, 38 wt.% concentrated HCl was added dropwise to precipitate it, and the mixture was washed with 10 wt.% ethanol and dried to obtain a lignin-based flame retardant.
[0031] Example 5
[0032] 2.7 g Kraft lignin, 4 g 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4.5 g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g benzaldehyde were suspended in 90 mL ethanol and reacted at 80° C. for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, to which 38 wt.% concentrated HCl was added dropwise to precipitate it, and the mixture was washed with 10 wt.% ethanol and dried to obtain a lignin-based flame retardant.
[0033] Example 6
[0034] 2.7 g Kraft lignin, 4 g 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4 g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g 4-methoxybenzaldehyde were suspended in 100 mL ethanol and reacted at 80° C. for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, 38 wt.% concentrated HCl was added dropwise thereto to precipitate it, and the mixture was washed with 10 wt.% ethanol and dried to obtain a lignin-based flame retardant.
[0035] Example 7
[0036] 2.7 g of enzymatic lignin, 3 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 3.5 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of benzaldehyde were suspended in 50 mL of ethanol and reacted at 80 ° C for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, 38 wt.% concentrated HCl was added dropwise thereto to precipitate it, and the lignin-based flame retardant was obtained by washing with 10 wt.% ethanol and drying.
[0037] Example 8
[0038] 2.7 g of enzymatic lignin, 3.5 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 3.5 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of 4-methylbenzaldehyde were suspended in 80 mL of ethanol and reacted at 80 ° C for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, 38 wt.% concentrated HCl was added dropwise thereto to precipitate it, and the lignin-based flame retardant was obtained by washing with 10 wt.% ethanol and drying.
[0039] Example 9
[0040] 2.7 g of enzymatically hydrolyzed lignin, 3.5 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of 4-ethylbenzaldehyde were suspended in 90 mL of ethanol and reacted at 80° C. for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, to which 38 wt.% concentrated HCl was added dropwise to precipitate it, and the solution was washed with 10 wt.% ethanol and dried to obtain a lignin-based flame retardant.
[0041] Example 10
[0042] 2.7 g of enzymatically hydrolyzed lignin, 4 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4.5 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of p-hydroxybenzaldehyde were suspended in 100 mL of ethanol and reacted at 80° C. for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, to which 38 wt.% concentrated HCl was added dropwise to precipitate it, and the solution was washed with 10 wt.% ethanol and dried to obtain a lignin-based flame retardant.
[0043] Embodiment 11
[0044] 2.7 g of organic solvent-based lignin, 3 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 3.5 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of benzaldehyde were suspended in 50 mL of ethanol and reacted at 80° C. for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, to which 38 wt.% concentrated HCl was added dropwise to precipitate it, and the mixture was washed with 10 wt.% ethanol and dried to obtain a lignin-based flame retardant.
[0045] Example 12
[0046] 2.7 g of organic solvent-based lignin, 3.5 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of 4-methoxybenzaldehyde were suspended in 80 mL of ethanol and reacted at 80 ° C for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, 38 wt.% concentrated HCl was added dropwise thereto to precipitate it, and the lignin-based flame retardant was obtained by washing with 10 wt.% ethanol and drying.
[0047] The study shows (as shown in the table below) that the maximum weight loss temperature and residual carbon value of lignin flame retardant are greater than those of enzymatic lignin, which are 360.4℃ and 69.18% respectively. Compared with enzymatic lignin, the residual carbon rate of lignin flame retardant is increased by 48%. The thermal stability of lignin flame retardant is significantly improved, which is related to the flame retardant effect of P element in the gas, the non-flammable gas released by the decomposition of N element and the inorganic oxygen-insulating protective layer generated by Si element. The results show that the thermal stability of lignin is significantly improved through nitrogen, phosphorus and silicon modification.
[0048] Table 1 Thermogravimetric analysis of lignin in Example 5
[0049]
[0050] Initial degradation temperature (T5%), maximum weight loss temperature (T max ) and carbon residue (Char)
[0051] Example 13
[0052] 2.7 g of organic solvent-based lignin, 4 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of p-hydroxybenzaldehyde were suspended in 90 mL of ethanol and reacted at 80° C. for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, to which 38 wt.% concentrated HCl was added dropwise to precipitate it, and the mixture was washed with 10 wt.% ethanol and dried to obtain a lignin-based flame retardant.
[0053] Embodiment 14
[0054] 2.7 g of organic solvent-based lignin, 4 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4.5 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of 4-methylbenzaldehyde were suspended in 100 mL of ethanol and reacted at 80° C. for 10 min using a microwave reactor. After the reaction was completed, the reaction solution was poured into a 40 wt.% NaOH solution, to which 38 wt.% concentrated HCl was added dropwise to precipitate it, and the mixture was washed with 10 wt.% ethanol and dried to obtain a lignin-based flame retardant.
[0055] Embodiment 15
[0056] Method for modifying phenolic foam with lignin flame retardant: replace part of phenol (0, 5%, 10%) with lignin flame retardant, and prepare phenolic foam according to the phenol / formaldehyde molar ratio of 1:1.7. Add a certain amount of modified lignin, phenol (as shown in the table below) and 12.4g of deionized water to a 1000mL round-bottom four-necked flask equipped with a mechanical stirrer, a condenser and a thermometer, and place it in a 65°C water bath. Add polyformaldehyde four times every 15 minutes, and adjust the pH value of the mixture to 8-9 with 30wt.% NaOH solution. Then react at 70°C for 2.5h, then heat to 92°C and keep for 10min. When the temperature drops to 85°C, add 18.6g of melamine to obtain a modified phenolic resin (NPSiLPRX).
[0057] The obtained nitrogen-phosphorus-silicon lignin-based phenolic resin (NPSiLPRX), surfactant (Tween-80) and foaming agent (n-pentane) were placed in a plastic container according to Table 2. A curing agent (mixed acid) consisting of water, sulfuric acid and phosphoric acid (mass ratio 1:1:1) was added under vigorous stirring to form a uniform mixture. The obtained mixture was quickly poured into a mold (20 cm × 20 cm × 5 cm) and heated in a preheated oven at 75 ° C for 3 hours to complete the curing and foaming process. The obtained phenolic foam was named NPSiLPFX, where X is the substitution rate of modified lignin.
[0058] Table 2 Formulas of lignin-based phenolic foams with different substitution rates of nitrogen, phosphorus and silicon
[0059]
[0060] The above examples are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nitrogen-phosphorus-silicon-containing lignin flame retardant, characterized in that: The steps are as follows: according to the proportion, 2.7 g of lignin, 3-4 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 3.5-4.5 g of DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g of aromatic aldehyde are suspended in 50-100 mL of ethanol, reacted in a microwave reactor at 80° C. for 8-12 minutes, poured the reaction solution into a NaOH solution, added HCl dropwise thereto to precipitate it, washed with ethanol and dried to obtain an intrinsic lignin-based flame retardant containing nitrogen, phosphorus and silicon.
2. The method for preparing the nitrogen-phosphorus-silicon lignin flame retardant according to claim 1, characterized in that: The lignin is at least one of Kraft lignin, organic solvent lignin or enzymatic lignin.
3. The method for preparing the nitrogen-phosphorus-silicon lignin flame retardant according to claim 1, characterized in that: The aromatic aldehyde is benzaldehyde, 4-methylbenzaldehyde, 4-ethylbenzaldehyde, 4-methoxybenzaldehyde or p-hydroxybenzaldehyde.
4. The method for preparing the nitrogen-phosphorus-silicon-containing lignin flame retardant according to claim 1, characterized in that: The specific steps are as follows: 2.7 g Kraft lignin, 4 g 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 4.5 g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and 1.03 g benzaldehyde are suspended in 90 mL ethanol, and reacted at 80°C for 10 minutes using a microwave reactor. After the reaction is completed, the reaction solution is poured into a 40wt.% NaOH solution, 38wt.% concentrated HCl is added dropwise thereto to precipitate it, and the lignin-based flame retardant is obtained by washing with 10wt.% ethanol and drying.
5. The nitrogen-phosphorus-silicon-containing lignin flame retardant prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the nitrogen-phosphorus-silicon-containing lignin flame retardant according to claim 5 in the preparation of phenolic foam.
7. The use according to claim 6, characterized in that: 10% of phenol was replaced by lignin flame retardant, and phenolic foam was prepared according to the phenol / formaldehyde molar ratio of 1:1.7; 28g of lignin flame retardant, 252g of phenol and 12.4g of deionized water were placed in a 65℃ water bath, 120g of polyformaldehyde was added four times every 15 minutes, and the pH value of the mixture was adjusted to 8-9 with 30 wt.% NaOH solution; then the reaction was carried out at 70℃ for 2.5 hours, and then the temperature was raised to 92℃ and maintained for 10 minutes. When the temperature dropped to 85℃, 18.6g of melamine was added to obtain a modified phenolic resin; the obtained phenolic resin, 4g of surfactant and 10.5g of foaming agent were put into a plastic container, and 28g of a mixed acid composed of water, sulfuric acid and phosphoric acid in a mass ratio of 1:1:1 was added under stirring to form a uniform mixture, and the obtained mixture was poured into a mold and heated at 75℃ for 3 hours to complete the curing and foaming process.
Citation Information
Patent Citations
A toughened lignin flame retardant and its preparation method and application
CN115947953B